Pengembangan sistem informasi berbasis komputer untuk eﬁ siensi penyelenggaraan makanan di Instalasi Gizi RS Militer Malang - Hasan Aroni; Hari Kusnanto; Anis Fuad (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2013)
ABSTRACTBackground: The rapid development of science and technology in the globalization era, particularly information technology enables data or information to be processed quickly and accurately. Nutrition service in the form of food provision in hospitals requires precision and accuracy  as well as speed in its process. Therefore the utilization of science and technology especially computer-based information system will be of much help. Nutrition installation of Malang Military Hospital still uses manual method in calculating the need for food stock so that it needs more time and nutrition staff to do the work.    Method: The study was a quasi experimental study (before and after) without control group to ﬁ nd out the difference in duration of food stock need calculation before and after the implementation of computer-based information system in the food provision at Nutrition Installation of Malang Military Hospital.Result: The implementation of computer-based information system at nutrition installation improved nutrition staff and time efﬁ ciency in the calculation of food stock needs. Only one nutrition staff was needed to operate computer, whereas in the manual calculation method two nutrition staff were needed to do the work. The time needed to calculate food stock before the implementation of computer-based information system in average was 3.5 hours and after the implementation was 1.6 hours, based on statistical test at signiﬁ cance level 95% p<α(0.05) whereby 0.003<0.05. This meant there was difference in duration of time needed before and after the implementation of computer-based information system in food provision at Nutrition Installation of Malang Military Hospital.Conclusion: The development of computer-based information system improved nutrition staff and time efﬁ ciency in the calculation of food stock need in food provision at Nutrition Installation of Malang Military Hospital.KEYWORDS: information system, efﬁ ciency, food stock calculation, nutrition installation, food provisionABSTRAKLatar Belakang: Perkembangan iptek pada era globalisasi yang begitu pesat, terutama teknologi informasi akan memungkinkan proses data atau informasi dengan cepat dan akurat. Pelayanan gizi, dalam hal penyelenggaraan makanan rumah sakit dalam prosesnya memerlukan ketelitian dan ketepatan serta kecepatan waktu yang digunakan. Untuk itu, pemanfaatan ilmu pengetahuan dan teknolgi dalam hal ini sistem informasi berbasis komputer akan sangat membantu. Instalasi Gizi Rumah Sakit Militer Malang (RSMM), dalam kegiatan perhitungan kebutuhan bahan makanan masih menggunakan penghitungan secara manual sehingga memerlukan waktu dan tenaga kerja gizi yang lebih untuk menyelesaikannya.Tujuan: Mengembangkan sistem informasi berbasis komputer untuk meningkatkan eﬁ siensi waktu dan tenaga kerja gizi dalam perhitungan kebutuhan bahan makanan pada penyelenggaraan makanan di Instalasi Gizi RSMM.Metode: Penelitian ini merupakan penelitian quasi experimental (before-after) tanpa kelompok kontrol untuk mengetahui perbedaan durasi waktu yang digunakan dalam perhitungan kebutuhan bahan makanan sebelum dan sesudah menerapkan sistem informasi berbasis komputer pada penyelenggaraan makanan di Instalasi Gizi RSMM.Hasil: Penelitian ini menunjukkan bahwa dengan penerapan sistem informasi berbasis komputer pada instalasi gizi akan meningkatkan eﬁ siensi tenaga kerja gizi dan waktu dalam perhitungan kebutuhan bahan makanan. Satu tenaga kerja gizi cukup digunakan untuk operasional computer yangsebelumnya 2 tenaga kerja gizi untuk perhitungan secara manual. Waktu yang diperlukan untuk perhitungan bahan makanan sebelum dan sesudah menerapkan sistem informasi berbasis komputer berbeda nyata dengan rata-rata adalah 3,5 jam dan 1,6 jam(p<0,05).Kesimpulan: Pengembangan sistem informasi berbasis komputer akan meningkatkan eﬁ siensi tenaga kerja gizi dan waktu dalam perhitungan kebutuhan bahan makanan pada penyelenggaraan makanan di Instalasi Gizi RSMM.KATA KUNCI: sistem Informasi, komputer, eﬁ siensi tenaga kerja gizi dan waktu, perhitungan kebutuhan bahan makanan